Video - Quin, John (Emerald Publishing Limited, 2023)
Video is everywhere. But what is video art and how does it differ from cinema? What connections has it made with healthcare and medicine? And what implications might these connections have for how we approach our physical and mental health? Breaking new ground, Video acts as an accessible introduction to the potential value of this medium within medical practice, patient care and everyday creative expression. Pairing examples with specific health conditions and themes, author John Quin presents a series of video artworks and their potential benefit for patients, clinicians and carers. Heeding the rise of "amateur' forms of video-making, shared through platforms such as YouTube, TikTok and Instagram, Quin also considers how the wide reach and convenience of social media is impacting health and wellbeing as popular interest in the medium continues to evolve. Featuring suggestions for both further reading and further viewing, Video navigates uncharted territory on behalf of artists, medical professionals and anyone interested in how video deals with health.
Keywords: Arts -- Therapeutic use.; Creative ability.; Internet videos.; Medical -- Mental Health.; Mental health services.; elektronické knihy; electronic books